2007
DOI: 10.1038/ncb1546
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative demethylation by JMJD2C and LSD1 promotes androgen receptor-dependent gene expression

Abstract: Posttranslational modifications of histones, such as methylation, regulate chromatin structure and gene expression. Recently, lysine-specific demethylase 1 (LSD1), the first histone demethylase, was identified. LSD1 interacts with the androgen receptor and promotes androgen-dependent transcription of target genes by ligand-induced demethylation of mono- and dimethylated histone H3 at Lys 9 (H3K9) only. Here, we identify the Jumonji C (JMJC) domain-containing protein JMJD2C as the first histone tridemethylase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
481
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(497 citation statements)
references
References 23 publications
12
481
1
1
Order By: Relevance
“…Wissmann and colleagues [41] have demonstrated that JMJD2C, which demethylases H3K9me3, and LSD1, which specifically demethylases H3K9 me2/me1, interact and cooperatively stimulate AR-dependent gene transcription. Recently it has been also reported, in ERa regulated transcription, a coordinated interaction among ERa and the H3K9me3 demethylase JMJD2B, and the H3K4 methyltransferase MLL2 complex has been recently reported [42].…”
Section: Discussionmentioning
confidence: 99%
“…Wissmann and colleagues [41] have demonstrated that JMJD2C, which demethylases H3K9me3, and LSD1, which specifically demethylases H3K9 me2/me1, interact and cooperatively stimulate AR-dependent gene transcription. Recently it has been also reported, in ERa regulated transcription, a coordinated interaction among ERa and the H3K9me3 demethylase JMJD2B, and the H3K4 methyltransferase MLL2 complex has been recently reported [42].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, epigenetic enzymes interpreting and modifying histones are often aberrantly expressed in PrCa (Cooper and Foster, 2009), such as class I HDACs, which are overexpressed in aggressive and hormone-refractory PrCa, thus contributing to androgen-independent, lethal PrCa's (Halkidou et al, 2004;Weichert et al, 2008). Eight KDMs are highly expressed in PrCa's (Metzger et al, 2005;Kahl et al, 2006;Wissmann et al, 2007). Various HDACs and KDMs were shown to regulate androgen receptor (AR)-mediated transcription, thus affecting gene expression patterns essential for PrCa proliferation, development and progression (Yamane et al, 2006;Wissmann et al, 2007;Wolf et al, 2007;Xiang et al, 2007;Welsbie et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Both amine oxidases and JmjC-domain proteins demethylate by oxidation or hydroxylation, processes directly affected under hypoxia [21]. One potential mechanism driving increased H3K4me3 may be hypoxia-induced inactivation of H3K4me3-specfic histone demethylases, which utilize molecular oxygen during enzymatic removal of methyl groups [22][23][24]. The observed modifications of histones provide a hypoxia-regulated platform for binding and interactions of additional chromatin modifiers, remodelers or regulators of transcription, further amplifying gene-specific response to hypoxic stress.…”
Section: Hypoxia-induced Gene-specific Histone Modificationsmentioning
confidence: 99%